THE INCIDENCE OF SWIMMING-INDUCED PULMONARY OEDEMA DURING MASS-PARTICIPATION TRIATHLON RACES: OPTIMISING ATHLETE SAFETY. Issue 4 (1st February 2017) - Smith, Ralph; Parkin, James; Knight, Nick; Kipps, Courtney
Abstract : Background: Swimming Induced Pulmonary Edema (SIPE) is life-threatening condition that can affect healthy triathletes. There have been several reported cases amongst triathletes, however the current estimation of incidence is derived from a survey of triathletes with self-reported symptoms suggestive of SIPE. Objective: To investigate the incidence of SIPE and associated risk factors in mass participation Triathlon Competitions (TC). Design: A retrospective analysis of Competitors' Medical Records (CMR). Setting: 11 consecutive UK-based TCs between 2011 and 2016. The competitions involved elite and non-elite competitors who raced Super Sprint, Sprint, Olympic and Olympic Plus distances. Participants: CMR of patients presenting to Triathlon Medical Team (TMT) with medical complaints/injuries were analysed. Those diagnosed with SIPE were included. Diagnostic criteria included absence of water aspiration, acute onset of dyspnoea, cough and/or expectoration of frothy sputum, with evidence of pulmonary oedema on physical examination. Assessment of Risk Factors: Patients' Age, gender, race distance, co-morbidities and medical management were recorded. Main Outcome Measurements: The incidence of SIPE in TCs. Results: 68557 competitors started the TCs and 429 competitors presented to the TMT. Five case of SIPE were recorded, giving rise to an incidence of 0.73/10, 000 competitors and 1.2% of all presentations to the TMT. Mean age was 42 (21–58) and a third were female. All were non-elite athletes competing in a variety of race distances; one patient had pre-existing cardiac comorbidities; and in 3 cases participants were competing in their first triathlon. All required supplementary oxygen and transfer to hospital for definitive management. Conclusion: This report is the first to describe the incidence of SIPE in mass participation triathlon competitions. Event organisers and TMTs should be prepared for competitors developing SIPE which appears not to be bound by age, gender, race distance or co-morbidities. Further research is required to identity those who are at risk of SIPE.